Reliability of caspase activity as a biomarker of hepatic apoptosis in nonalcoholic fatty liver disease - TOPTAŞ, TAYFUR (My University, 2011)
A letter in response to: Yilmaz Y, Kurt R, Kalayci C. Apoptosis in nonalcoholic steatohepatitis with normal aminotransferase values: zooming in on cytokeratin 18 fragments. Biomarkers Med. 4(5), 743–745 (2010).